WSN based sensing model for smart crowed movement with identification: an extended study - Nawaz, Naeem A.; Waqas, Ahmad; Muhammed Yusof, Zulkefli; Mahesar, Abdul Waheed; Shah, Asadullah (JATIT & LLS, 2017)
With the advancement of IT and increase in world population rate, Crowed Management ( CM) has become a subject undergoing intense study among researchers. Technology providers fast and easily available means of transport and up-dates information access to the people that cause crowed at public places. This imposes a big challenge for crowed safety and security at public places such as airports, railway stations and check points. For example, crowed of pilgrims during Hajj and Ummrah while crossing the borders of Makkah, Kingdom of Saudi Arabia. To minimize the risk of such crowed safety and security, identification and verification of people is necessary which caused unwanted increment in processing time. It is observed that managing crowed during specific time period ( Hajj and Ummrah) with identification and verification became challenge. At present, many advanced technologies such as Internet of Things (IoT) are being used to solve the crowed management problem with minimal processing time. In this paper, we have presented a wireless sensor Network (WSN) based conceptual model for smart crowed movement with optimal verification of cluster members (CMs) and leads to minimal processing time for people identifications. This handles the crowed by forming groups and provides proactive support to handle them in organized manner. As a result, crowed can be managed to move safely from one place to another with group identification. By controlling the drop rate or unverified CMs rate, the performance of the smart movement can be increased. This decrease or control of the drop rate will also minimize the processing time and move the crowed in smart way.